The pledge of allegiance - Chang, Kirsten (Minneapolis, MN : Bellwether Media, 2019)
This book introduces the Pledge of Allegiance to young readers through leveled text and related photos.
Includes bibliographical references (page 23) and index.
2.1
K-3
440L
K
Keywords: Bellamy, Francis. -- History -- Juvenile literature; Flags -- United States -- History -- Juvenile literature; Bellamy, Francis. -- History; Flags -- United States -- History; Readers (Elementary) -- Nonfiction